Navigating complex social landscapes: examining care experienced young people's engagements with sport and physical activity. Issue 1 (2nd January 2021) - Sandford, Rachel; Quarmby, Thomas; Hooper, Oliver; Duncombe, Rebecca
ABSTRACT: Internationally, there has been growing interest in the experiences of care experienced youth and their engagements with activities that can support positive development. Despite the acknowledged potential of sport/physical activity (PA) to act as a vehicle for positive development, there remain concerns about the piecemeal nature of sport/PA opportunities for care experienced youth at a local level and their capacity to access these. To date, relatively few studies have considered the role of sport/PA within the day-to-day lives of care experienced young people and, furthermore, these have often drawn more on the voices of adults than care experienced youth themselves. In response, the 'Right to be Active' (R2BA) project was developed to examine care experienced youth's perspectives on/experiences of sport/PA. This paper seeks to provide a broad overview of the study and discusses key empirical findings. Adopting a predominantly qualitative, participatory approach, R2BA comprised four interconnected phases: (1) a rapid review of policy documents; (2) the distribution of adult and young people surveys; (3) focus group interviews with 63 care experienced youth; and (4) repeat focus groups with 40 care experienced youth. Informed by Bourdieu's theoretical concepts and his perspectives regarding the multi-dimensional nature of social life, the analysis of data highlights the complex social landscapes that care experienced youth navigate on a day-to-day basis. Moreover, it demonstrates how the configuration of key factors (activities, places and people) can be influential in shaping care experienced youths' attitudes towards, participation in and experiences of sport/PA within the broader field of the care context. It is argued that the study points to the need for a more holistic understanding of care experienced young people's lives and for more thought to be given as to how different stakeholder groups can work in partnership to facilitate this population's access to/engagements in sport/PA.